The Poetics of the Literary Text: An Approach to Adib Kamal al-Din’s Collection of The Letter and the Crow is the title of a study - Jaddoua , Ass.Lecture Muhammad Fadil (Thi Qar Arts Journal, 2023)
This study aims to explore the language of an Iraqi poet known for his abundant poetic production and his distinctive style. Since his first work (Details) in 1976, Adib Kamal al-Din has been developing his poetic publications in a language that is not harsh to the contemporary reader, rejecting the strangeness of paving and the enormity of metaphor and its meaning. It tends to shape meaning and its horizons without manipulation or roughness, without "delirious" flipping of the positions of rhetoric. The recipient does not think that he tends towards ordinary language, but I will say that he writes poetry in our day and age. His poetry generally celebrates clear verbal formation, bursting with renewal, not confined to the private cemetery of vocabulary, in a language that belongs to a time when its life tools touch the far ends of the earth, a living language that the poet understands and practices its temptations by shaping it into poems and lives. This is what motivated us to study his collection (The Letter and the Crow) and approach its dominant language on various poems of the collection, where the language of nature and its poetry dominated, and the language of lamentation and its new being different from the pattern of classical Arab lamentation. Writing seeks difference at the level of language and topics in a way that the poet Adib Kamal al-Din knows how to pave its letters.